THE PERFECTION OF A METHOD OF NUMERICAL MODELING STEEL-AND-REINFORCED CONCRETE PRESSURE WATER PIPES - S V Bogachenko (Structural Mechanics of Engineering Constructions and Buildings, 2012)
The results of calculations of stress-strain state of steel-and-reinforced concrete pressure water pipes of the hydro station are presented. It was made with the help of a method of numerical modeling derived by the author. Numerical results were compared with experimental data obtained before.